The existence of an ideal leader's role in controlling employee performance - Engga Lift Irwanto; Yunia Wardi (Institute of Computer Science (IOCS), 2023)
A leader is likened to a spear to determine the success or failure of an organization he leads. When a leader is able to maintain the stability of his organizational system, then of course the organization can run well. A director (leader) at the Padang Regional General Hospital has the duty to control the performance of his employees in order to provide excellent health services to patients and the public. This research is a joint effort that combines literature research and field research, where it is expected to contribute to the development of knowledge, especially in the fields of leadership and organization. The research method used is to use literature and field approach techniques to analyze what conditions and situations are ideal for carrying out leadership in Padang Pariaman Hospital. The informants in this study are all existing employees, including directors, heads of administration, and personnel staff. The results of the study show that, in general, the leadership of the hospital has fully implemented its role as a leader in improving employee performance, while the role carried out by the leadership of the hospital is to guide and direct employees, encourage employees to follow in their footsteps, and be responsible. It's just that some employees have not carried out their duties with discipline. In this case, employees need to improve their performance as employees, while what needs to be improved from employees is the quality, quantity, and completion of work.